The Effect of Equivalent Rate, Bank Indonesia Sharia Certificate And Office Channeling On Third Party Funds With Profitability As Moderating Variables - Ayu Evita Nila; Taufikur Rahman (Islamic Accounting Journal, 2022)
This scientific research aims to determine the effect of the Equivalent Rate, Bank Indonesia Syariah Certificates and Office Channeling on Third Party Funds with Profitability as Moderation Variable for Indonesian Islamic Commercial Banks. The method used is a quantitative research method with a population of all Islamic Commercial Banks registered with the Financial Services Authority. The sample used in the study was determined through a purposive sampling method with several criteria that have been determined by the author so that there are 60 samples for the period 2016 to 2020. The data used are panel data types. The analytical test methods include descriptive statistical test, stationarity test, multiple regression test, T test, F test, R2, classical assumption test and Moderated Regression Analysis (MRA) test. The test was carried out using the Eviews 10 software tool. The results obtained showed that the Equivalent Rate variable had a significant positive effect on Third Party Funds. The Bank Indonesia Syariah Certificates variable has a significant negative effect on Third Party Funds and the Office Channeling variable has a significant positive effect on Third Party Funds. Based on the results of the MRA test, the profitability interaction variable cannot moderate the effect of the Equivalent Rate, Bank Indonesia Syariah Certificates and Office Channeling variables on Third Party Funds.Keywords: Equivalent Rate, Bank Indonesia Syariah Certificates, Office Channeling, Profitability and Third Party Funds